Association of glucose-lowering medications with cardiovascular outcomes: an umbrella review and evidence map. Issue 3 (March 2020) - Zhu, Jianhong; Yu, Xiaoxia; Zheng, Yayuan; Li, Jianfang; Wang, Yong; Lin, Yin; He, Zhichao; Zhao, Wenxia; Chen, Chuxiong; Qiu, Kaifeng; Wu, Junyan
Summary: Background: Considering the global burden of diabetes and associated cardiovascular disease, an urgent need exists for the best treatment, which should be based on the best available evidence. We examined the association between glucose-lowering medications and a broad range of cardiovascular outcomes, and assessed the strength of evidence for these associations. Methods: For this umbrella review we searched PubMed, Embase, and the Cochrane Library to identify systematic reviews and meta-analyses of randomised controlled trials examining the cardiovascular safety of glucose-lowering medications. Cardiovascular outcomes examined included major adverse cardiovascular events, cardiovascular death, myocardial infarction, stroke, heart failure, unstable angina, and atrial fibrillation. For each meta-analysis, we estimated the relative risk (RR) and 95% CI. We also created an evidence map showing the plausible benefits or harms of each intervention and the certainty of the evidence. Findings: We examined 232 meta-analyses evaluating ten classes of diabetes drugs. We identified six risk and 38 protective associations showing a high strength of evidence. Six associations increased the risk of cardiovascular disease, including glimepiride (stroke [RR 2·01; 95% CI 1·02–3·98]), rosiglitazone (myocardial infarction [1·28; 1·02–1·62] and heart failure [1·72, 1·31–2·27]), and pioglitazone (heart failure [1·40; 1·16–1·69]). 38 associations decreased the risk of cardiovascular disease, including glucagon-like peptide-1 receptor agonists as a class (major adverse cardiovascular events [RR 0·88; 95% CI 0·84–0·92], death from cardiovascular disease [0·87; 0·81–0·94], myocardial infarction [0·92; 0·86–0·99], stroke [0·84; 0·77–0·93], and heart failure [0·90; 0·83–0·99]), albiglutide (major adverse cardiovascular events [0·81; 0·68–0·96], myocardial infarction [0·77; 0·64–0·92], and heart failure [0·71; 0·55–0·93]), dulaglutide (stroke [0·78; 0·64–0·96]), exenatide (major adverse cardiovascular events [0·91; 0·83–1·00]), liraglutide (major adverse cardiovascular events [0·86; 0·77–0·96]), semaglutide (major adverse cardiovascular events [0·76; 0·62–0·92] and stroke [0·67; 0·45–1·00]), sodium-glucose co-transporter-2 inhibitors as a class (major adverse cardiovascular events [0·87; 0·82–0·93], death from cardiovascular disease [0·82; 0·75–0·90], myocardial infarction [0·86; 0·78–0·94], and heart failure [0·68; 0·63–0·73]), canagliflozin (major adverse cardiovascular events [0·84; 0·75–0·93], death from cardiovascular disease [0·82; 0·71–0·96], and heart failure [0·65; 0·54–0·78]), dapagliflozin (heart failure [0·70; 0·60–0·82]), empagliflozin (major adverse cardiovascular events [0·85; 0·77–0·94], death from cardiovascular disease [0·62; 0·50–0·78], and heart failure [0·64; 0·53–0·77]), and pioglitazone (major adverse cardiovascular events [0·84; 0·74–0·96], myocardial infarction [0·80; 0·67–0·95], and stroke [0·79; 0·65–0·95]). Interpretation: We found varied levels of evidence for the associations between diabetes drugs and cardiovascular outcomes; some drugs raised the risk of cardiovascular disease, whereas others showed benefit. Funding: None.